The Effect Of Good Governance And The Implementation Of Integrity Zones On Corruption Prevention (A Study On Skpd Apparatus In North Sumatra Province) - Salman Farizi; Rahima Purba; Renny Maisyarah (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of good governance and the implementation of the Integrity Zone on corruption prevention among regional government apparatus in North Sumatra Province. The urgency of this research is based on the importance of strengthening regional governance in suppressing corrupt practices. The study used a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. Data were collected through questionnaires from 80 respondents from regional government apparatus. The results show that good governance and the implementation of the Integrity Zone have a positive and significant effect on corruption prevention. This finding indicates that the implementation of good governance and the Integrity Zone are effective in suppressing corrupt behavior. The novelty of this research lies in its theoretical and practical contributions to strengthening bureaucratic reform and regional corruption prevention policies